Achievements in nanomineralogy - Osovetsky B.M. (Федеральное государственное бюджетное образовательное учреждение высшего профессионального образования «Пермский государственный национальный исследовательский университет», 2017)
The results of investigations in the field of nanomineralogy obtained by the Nanomineralogy Sector staff during 5 years (2012-2016) are presented. These include results of researches with the application of high-resolution electron microscopy with mi-croprobe analysis and experimental data. The study objects were unusual grains of placer gold of the Urals, Siberia (Russia), Kazakhstan, and the Yukon Territory (Canada). It is concluded that there are nanogold aggregation processes which lead to the formation of globular and "new" gold. These processes may be used in modern technologies of gold extraction.
Keywords: NANOGOLD; ELECTRON MICROSCOPY; AGGREGATION; TECHNOLOGY; НАНОЗОЛОТО; ЭЛЕКТРОННАЯ МИКРОСКОПИЯ; АГРЕГАЦИЯ; ТЕХНОЛОГИЯ; 549.283